Pojem "sodišča" in "sodne odločbe" v evropskem civilnem procesnem pravu? - Galič, Aleš (Pravni letopis, 2025)
The definition of the terms "court" and "judicial decision" in European civil procedural law is important for resolving traditional issues of private international law concerning the recognition and enforcement of foreign judicial decisions. It is also significant from the perspective of the broader constitutional dimensions of the position of the judiciary and judges in Member States, as well as from the perspective of the possible transfer of jurisdiction in certain matters to non-judicial authorities. It should not be overlooked that the concept of a court in EU regulations in the field of cooperation in civil and family matters is not regulated uniformly. The definition is most restrictive in the Brussels I Regulation, according to which only a court in the strict sense of national law qualifies as a court for the purposes of the Regulation. The definition in the Succession Regulation is broader, allowing for the inclusion of notaries, for example, but only insofar as they can decide on non-contentious matters which do not constitute a judicial function within the meaning of EU law, only if they act pursuant to a delegation of power or work under the control of a court. The broadest definition is found in the Brussels II Regulation, which refers entirely to the jurisdiction of a judicial or non-judicial authority under national law, without imposing any additional requirements.
Keywords: court; EU law; international jurisdiction; judgment; judicial function; mednarodna pristojnost; pravo EU; priznanje in izvršitev; recognition and enforcement; sodba; Sodbe; Sodišča; sodišče; sodna funkcija